Reconstitution of protein translocation from detergent-solubilized Escherichia coli inverted vesicles: PrlA protein-deficient vesicles efficiently translocate precursor proteins. - Watanabe, M (1990)
Proteoliposomes were reconstituted by detergent dialysis of a sodium cholate extract of inverted vesicles derived from Escherichia coli plasma membrane. The translocation of precursor proteins into reconstituted vesicles occurred at high efficiency and was SecB dependent. The protein composition of the reconstituted vesicles differed markedly from that of native vesicles. Immunoblot analysis of the sodium cholate extract and of the reconstituted vesicles indicated that PrlA (SecY) protein remained largely unsolubilized under the described conditions and was virtually absent from the reconstituted vesicles, suggesting that PrlA may not be required for in vitro translocation.